Características vocais de crianças disfônicas - Hoffmann, Carla Franco (2014)
Objective: to verify the auditory perceptual and acoustic vocal aspects and Maximum Phonation Time (MPT) of dysphonic children from 4:00 to 7:11 years old and verify the occurrence of dysphonia in the city of Santa Maria/RS/Brazil. Methods: were evaluated 307 children from 4:00 to 7:11 years old from different educational institutions by applying the assessment scale of auditory perceptual evaluation CAPE-V. Those who presented general degree of alteration higher than one were considered dysphonic. Collection of MPT, auditory perceptual voice analysis by CAPE-V scale and acoustic (programs Multi Dimensional Voice Program and Advanced Real Time Spectrogram). Statistical tests Kruskall Wallis, Spearman and Post Hoc. Results: 115 children (37,5%), with most percentage of boys, were considered dysphonic, and the number of children with normal voice was established in 192 (62,54%) most children presented a general degree and all the parameters of roughness, breathiness and strain into moderated and low MPT degree. Acoustic measures of fundamental frequency (F0) and JITT decreased with age, the opposite occurred with MPT/i/. The measures relative average of frequency disturbance, voice turbulence index (VTI), and the number of sub harmonics were higher at age four and shimmer was greater at age of seven. There were negative correlations between: blackening of the tracing in of spectography of narrowband and broadband at high frequencies and vocal tension; between VTI and MPT; between degree of unvoiced segments and MPT. There was a positive correlation between smoothed amplitude perturbation quotient (sAPQ) and roughness. Conclusion: vocal characteristics of dysphonic children undergo changes with increasing age in some parameters of different vocal changes in children with normal voice. The occurrence of childhood dysphonia was close to other research, predominantly in males